Integration of an advanced practice nurse into a primary care practice: a qualitative analysis of experiences with changes in general practitioner professional roles in a Swiss multiprofessional primary care practice (Swiss Medical Weekly, 2022)
BACKGROUND: The complex care needs of people with chronic illnesses and multimorbidity pose a significant challenge to the Swiss primary care system. Ensuring efficient, high-quality care will require new care models. Internationally, the integration of advanced practice nurses (APNs) into primary care models has shown promising results. The current study investigates how general practitioners (GPs) in Switzerland experience the integration of APNs into their primary care teams with respect to their own professional roles.METHODS: We used a qualitative, social-constructivist approach, focusing on six individual interviews with general practitioners within the frame of a larger study including GPs and APNs in a Swiss multiprofessional primary care practice. Data were analysed following Braun and Clarke’s approach for reflexive thematic analysis.SETTING AND PARTICIPANTS: The study took place between August 2019 and February 2020 in a Swiss multiprofessional primary care practice that had been working with APNs for nine years. Participants included six general practitioners.RESULTS: We identified three main themes characterising Swiss GPs’ experiences with the integration of APNs into their primary care team: (1) trust as foundation for collaboration with APNs; (2) build-up of the APN role by delegation, teaching, and supervision, investing time particularly at the beginning of their collaboration with the APN — a time investment that declined significantly as the APNs’ competencies grew — and (3) synergies of partnership-based collaboration with APNs. Physicians who were experienced teachers and supervisors, and who delegated tasks based on who would be able to fulfil them most efficiently and effectively, experienced not only a broad range of synergies, but also possibilities to further develop the range of their own activities. Comprehensive, high-quality patient care was perceived as a particular added value.CONCLUSION: Our analysis revealed that GPs experienced interprofessional synergies when working collaboratively with APNs. These were rooted in trust and relied on abilities in teaching, supervision and delegation to achieve maximum impact. Capitalising on the integration of APNs into primary care, this new care model can be adapted to diverse individual settings. We conclude this article by highlighting the potential of working collaboratively with APNs, who play increasingly important roles in the primary care of polymorbid patients with complex needs.